2017
DOI: 10.3390/ma10111273
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Li(Ni0.6Co0.2Mn0.2)O2 Cathode Materials by Nano-Al2O3 to Improve Electrochemical Performance in Lithium-Ion Batteries

Abstract: Al2O3-coated Li(Ni0.6Co0.2Mn0.2)O2 cathode materials were prepared by simple surface modification in water media through a sol-gel process with a dispersant. The crystallinity and surface morphology of the samples were characterized through X-ray diffraction analysis and scanning electron microscopy observation. The Li(Ni0.6Co0.2Mn0.2)O2 cathode material was of a polycrystalline hexagonal structure and agglomerated with particles of approximately 0.3 to 0.8 μm in diameter. The nanosized Al2O3 particles of low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…[11] Single layer or multilayer coatings are formed on the surface of the material, whichc an transfer electrons or ions and protect the cathode from electrolyte corrosion. [12] Metal oxides or other polyanion materials such as Al 2 O 3 , [13] LaPO 4 , [14] TiP 2 O 7 , [15] Li 4 P 2 O 7 , [16] Li 3 PO 4 /PPy, [17] LiZr 2 (PO 4 ) 3 , [18] Li 1.4 Al 0.4 Ti 1.6 (PO 4 ) 3 , [19,20] Al 2 O 3 /LiAlO 2 , [21] and MoS 2 [22] have been reported to be very effective coating materials. Li et al [23] reported Zr modificationh ad dual functions, one is that Zr 4 + can enter into the lattice of the transition metal plane or lithium plane, the other is that the remaining Zr 4 + floats on the surface of particles, formed aL i 2 ZrO 3 coating layer.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Single layer or multilayer coatings are formed on the surface of the material, whichc an transfer electrons or ions and protect the cathode from electrolyte corrosion. [12] Metal oxides or other polyanion materials such as Al 2 O 3 , [13] LaPO 4 , [14] TiP 2 O 7 , [15] Li 4 P 2 O 7 , [16] Li 3 PO 4 /PPy, [17] LiZr 2 (PO 4 ) 3 , [18] Li 1.4 Al 0.4 Ti 1.6 (PO 4 ) 3 , [19,20] Al 2 O 3 /LiAlO 2 , [21] and MoS 2 [22] have been reported to be very effective coating materials. Li et al [23] reported Zr modificationh ad dual functions, one is that Zr 4 + can enter into the lattice of the transition metal plane or lithium plane, the other is that the remaining Zr 4 + floats on the surface of particles, formed aL i 2 ZrO 3 coating layer.…”
Section: Introductionmentioning
confidence: 99%
“…Limitations in the lifetime of lithium-ion batteries still reveal often to be an issue in battery applications as in automotive [8,9,10,11]. In recent years, Lithium Nickel Manganese Cobalt (NMC) for use in positive electrodes eventually offered improved cycle life, thermal stability and energy density capabilities for lithium-ion batteries [12,13,14,15]. Generally, charging and discharging capabilities of electrodes are mainly linked to their lithium ion solid phase diffusion coefficient, which is therefore recognised as a significant kinetic characteristic of Lithium ion intercalation electrode materials [16].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned before, the coating materials used in Ni‐rich materials include inorganics, organics, and some composite coating materials. For inorganics, the coating materials in recent works mainly include metal oxides (ZnO, [ 33 ] TiO 2 , [ 33‐37 ] Al 2 O 3 , [ 30,33,38‐42 ] ZrO 2 , [ 38,43‐46 ] Nb 2 O 3 , [ 47 ] Co 3 O 4 , [ 33,48 ] Cr 8 O 21 , [ 49 ] MgO, [ 38 ] MnO 2 , [ 50,51 ] V 2 O 3 , [ 33 ] and V 2 O 5 [ 52 ] ), metal fluorides (LiF, [ 53‐55 ] AlF 3 , [ 54,56 ] and FeF 3 [ 57 ] ), metal phosphates (LaPO 4 , [ 58‐60 ] FePO 4 , [ 61‐63 ] CoPO 4 , [ 62,63 ] AlPO 4 , [ 40,62,64‐65 ] and MnPO 4 [ 63,66 ] ), and some kinds of lithium compounds (LiBO 2 , [ 67 ] LiAlO 2 , [ 40,41,68‐71 ] Li 2 MoO 4 , [ 72 ] Li 2 ZrO 3 , [ 43,73‐74 ] Li 3 VO 4 , [ 75‐76 ] Li 3 PO 4 , [ 77‐78 ] Li 2 SiO 3 , [ 79‐81 ] Li 4 SiO 4 , [ 82 ] Li x Ti 2 O 4 , [ 70 ] Li 4 Ti 5 O 12 , [ 83‐84 ] LiZr 2 (PO 4 ) 3 , [ 85 ] and LiAlF 4 [ 54 ] ) and carbon materials (traditional carbon materials, [ 86‐88 ] modified carbon materials, [ 89‐90 ] carbon nanotube materials, […”
Section: Applications Of Coating In Ni‐rich Materialsmentioning
confidence: 99%
“…The coating materials could cover the surface of cathode materials thoroughly due to the introduction of solvent. Sometimes, the precursors of coating materials will even hydrolyze in solvent [ 34,70 ] or react with other substances [ 89,115 ] to form uniform coating layers. The strategies of wet coating methods in Ni‐rich materials include traditional wet coating method (to modify dry coating method [ 103 ] ) and wet chemical coating method (such as sol‐gel method, [ 56,74,116‐118 ] hydrothermal method, [ 41,68 ] and co‐precipitation method.…”
Section: Applications Of Coating In Ni‐rich Materialsmentioning
confidence: 99%